Evaluation of a modified outpatient model for using propranolol to treat infantile hemangiomas. Issue 4 (23rd May 2019) - Putterman, Elana; Wan, Joy; Streicher, Jenna L.; Yan, Albert C.
Abstract: Background: For infantile hemangiomas requiring treatment, existing recommendations advise initiation of propranolol followed by a 2‐hour period of blood pressure and heart rate monitoring, resulting in prolonged office visits for both families and clinicians. Objectives: In order to reduce visit times, we evaluate our current practice of at‐home or in‐office propranolol administration followed by in‐office vital sign monitoring. Methods: We retrospectively reviewed the medical records of 157 patients with infantile hemangiomas (IH) who initiated propranolol under this outpatient protocol. Blood pressure (BP) and heart rate (HR) were obtained at a baseline visit and 1‐2 hours after initial dose administration. We identified potential risk factors for clinically significant decreases in systolic blood pressure (SBP) and HR (defined as decrease of > 20 mm Hg and > 15 bpm, respectively) using logistic regression analysis, and adverse events were recorded. Results: Fifty‐five individuals (35.4%) showed a decrease in HR of more than 15 bpm, and 23 individuals (14.7%) showed a decrease in SBP of more than 20 mm Hg. Multivariable logistic regression suggested that younger age, history of preterm birth, and Caucasian race may slightly increase the odds of clinically significant changes in vital signs upon propranolol initiation. However, no clinically symptomatic adverse events occurred upon initiation of propranolol. Conclusions: Vital sign monitoring may be important when starting propranolol treatment in younger or historically preterm patients. However, routine mandatory in‐office vital sign monitoring may not be necessary in healthy infants more than 45 weeks postconceptional age.